Analyss of Heavy Metal Content of Copper (Cu) in Cork Fish From Rawa Taliwang Lake, West Sumbawa Regency 2021 - Galuh Chandra Kirana; Khairuddin Khairuddin; M. Yamin (Jurnal Biologi Tropis, 2022)
Rawa Taliwang Lake is the largest freshwater fish source in West Sumbawa Regency. Channa striata is a fish that is in great demand because of its health benefits. Fish are organisms that are used as bioindicators of heavy metals in waters. This study aims to determine the metal content of Copper (Cu) in Channa striata from Rawa Taliwang Lake and to find out Channa striata from Rawa Taliwang Lake is still suitable for consumption according to the copper metal contamination threshold in food. This research was conducted at Lake Rawa Taliwang in September-November 2021. Data collection was carried out by purposive sampling method at 2 research stations, namely the East side and the West side. The sample in this study were 4 Channa striata caught with fish traps. The samples were then analyzed for the content of copper (Cu) which was carried out at the BLKPK NTB Province using Atomic Absorption Spectrophotometry (AAS). The body part of the fish that is meticulous is the flesh of the fish that has been cleaned of scales and removed from the internal organs. The test results showed that the average metal content of copper (Cu) in Channa striata from Lake Rawa Taliwang was around 0.697 mg/kg (ppm). The content of copper metal (Cu) in Channa striata from Lake Rawa Taliwang is still below the maximum threshold for metal contamination in food in accordance with the Regulation of the Directorate General of Drug and Food Control Number: 03725/B/SK/VII/89 concerning the maximum threshold for metal contamination, namely 20.0 mg/kg.